Developing English Learning: An Innovative Online Instructional Model with an Inquiry-Based Approach - Syakur, Abd; Sutama, Sutama; Sutopo, Anam; Prasetya, Rizki; Prawoco, Fajar Sandi (Universitas Islam Negeri Raden Intan Lampung, 2023)
This research and development (R&D) activity aims to develop a reliable, practical, and effective inquiry learning model that includes preliminary research, product design and development, and assessment. In this development process, the stages outlined by Plomp and Nieveen are adopted. Forty pharmacy students from the pharmacy study program of a state university in Malang, East Java, took part in learning during the 2021-2022 academic year. A questionnaire with Likert Scale 4 categories is a research tool. The expert validation test revealed that